Exploring the Students' Mathematical Communication Skill through Online Discussion Activities in Google Classroom - Zaenal Abidin; Tri Mulyono Edi Saputro (SEAMEO SEAMOLEC, 2023)
Being communicative is one of the 21st century skills that students must have to face challenges of the industrial revolution 4.0 era. Communication is also an important part of Mathematics education. Writing and discussions are some forms of activities that can help to improve the students' mathematical communication skills. Specifically, the discussion session should not only done face-to-face, but can be done online through certain applications such as Google Classroom. This research tries to explore the students' mathematical communication skills in solving the mathematical problems provided by the teacher through online discussions. An ethnographic approach is used in this research to observe the students’ activities in Google Classroom in the online discussions both with the teacher and their peers. The results showed that the Google Classroom- assisted discussion sessions has good potential to support the improvement of the students' mathematical communication skills. Some positive potential for the students' active participation in the online discussions is that they were able to construct their knowledge to understand the mathematical concepts shown by finding mathematical solutions to mathematical contextual problems provided by the teacher. They were also increasingly accustomed to solving mathematical problems related to their real life.